2013
DOI: 10.1016/j.pnpbp.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-independent decrease in plasma dopamine beta-hydroxylase activity in Alzheimer's disease

Abstract: The noradrenergic system is involved in the etiology and progression of Alzheimer’s disease (AD) but its role is still unclear. Dopamine beta-hydroxylase (DBH) as a catecholamine-synthesizing enzyme plays a central role in noradrenaline (NA) synthesis and turnover. Plasma DBH (pDBH) activity shows wide inheritable interindividual variability that is under genetic control. The aim of this study was to determine pDBH activity, DBH (C-970T; rs1611115) and DBH (C1603T; rs6271) gene polymorphisms in 207 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 53 publications
0
29
0
1
Order By: Relevance
“…Many genes, such as apolipoprotein E (APOE) [62], triggering receptor expressed on myeloid cells 2 (TREM2) [63], and methylene tetrahydrofolate reductase (MTHFR) [64], in combination with environmental factors result in a network of interplay in AD development. DBH catalyzes the oxidative hydroxylation of DA to NE, and recent evidence indicated that NE is not only a risk factor but also an actual etiological factor of AD [22]. We collected seven studies on the association of DBH polymorphisms at three loci (rs1611115, rs5320, and rs1611131) with the risk of AD.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many genes, such as apolipoprotein E (APOE) [62], triggering receptor expressed on myeloid cells 2 (TREM2) [63], and methylene tetrahydrofolate reductase (MTHFR) [64], in combination with environmental factors result in a network of interplay in AD development. DBH catalyzes the oxidative hydroxylation of DA to NE, and recent evidence indicated that NE is not only a risk factor but also an actual etiological factor of AD [22]. We collected seven studies on the association of DBH polymorphisms at three loci (rs1611115, rs5320, and rs1611131) with the risk of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathological analysis of PD indicates that the retrogression of dopaminergic neurons in the substantia nigra leads to a DA deficiency in the corpus striatum [3]. The DBH enzyme is an important member of the DA system, and evidence has shown that under certain conditions, DBH can influence the NE levels in the brain [22]. In addition, previous studies found altered DBH activity in cerebrospinal fluid (CSF) [22], also suggesting that DBH might participate in the pathological mechanism of PD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations